Penyuluhan Hukum Undang-Undang Administrasi Pemerintahan - Vica Jillyan Edsti Saija; Novi Diana Permatasari; Flouransia Rananmasse; Lanny Selvia Leasa; Fahran Fesanrey (Faculty of Law Pattimura University, 2022)
Introduction: The lack of understanding of the community and office staff about the importance of laws and regulations for the administration of government brings its own legal problems for the community. This is the basis for consideration for carrying out community service activities in Wainitu ward, Nusaniwe sub-district in the form of socializing government administration law.Purposes of Devotion: Provide legal understanding of the laws and regulations of government administration to the community and the staff of Wainitu ward office, Nusaniwe sub-district, Ambon city. Method of Devotion: Method of dedication is using legal counseling to the community, especially Wainitu sub-district office employees.Results of the Devotion: The implementation of these activities is known that there are many problems in government administration, such as how to obtain authority, the function of government agencies to why discretion is issued. Besides that, there are issues in public services that occur in the community in the form of administrative services at the lurah office which are convoluted, slow and require money. Poor public services have an impact on public trust in the government.